ANALISIS STRATEGI PEMASARAN JASA - Puspaningtyas, Meinarti (DINAMIKA DOTCOM, 2011)
One goal of marketing is to influence consumers to be willing to buy goods or services marketed. Before a to-do marketing activities, companies must first study the behavior of konsumen.Dinamika almost all service markets has changed; the composition of the low level has led to fierce competition and intense. In this competitive marketplace, marketing has become key differentiator between success and corporate failure. Marketing gives attention to the dynamic reciprocal relationship between the products and services company, wants and needs of consumers and competitors activities. Distribution services, most are directly from producers to consumers, such as care services, medical, entertainment, laundry, barber shop and others. In a wider sense of insurance, and services provided by government is also a service. Service marketing requires not only external but also internal and interactive peasaran require. Mastery of services that are part of the marketing concept in general is an important study in an increasingly complex economic conditions and modern. The concept and analysis of service marketing strategy involves a wide variety of problems of study.Â Keywords: analysis, marketing and service